2011
DOI: 10.1097/pas.0b013e318233b0f7
|View full text |Cite
|
Sign up to set email alerts
|

Fallopian Tube Correlates of Ovarian Serous Borderline Tumors

Abstract: Ovarian serous borderline tumors (SBTs) are presumed to originate in the ovarian cortex or peritoneal surface. The pathogenetic role of the fallopian tube (FT) is unclear but recently, secretory cell outgrowths (SCOUTs) lacking PAX2 expression have been described in benign FTs. This study addressed 1) the differentiation characteristics of SBTs, 2) the frequency of SCOUTs lacking PAX2 expression in the fallopian tubes of patients with SBTs, and compared 3) SCOUT morphology and 4) PAX2 expression with SBTs. SBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 23 publications
4
46
1
Order By: Relevance
“…15 It is important to emphasize that PAX2-null SCOUTs with normal p53 expression appear to be distributed equally in fimbrial and proximal oviductal sections, shown by Chen et al 14 and confirmed in this report. Thus, the absence of PAX2-null SCOUTs in pediatric and post-partum sterilization tubal sections is significant despite the limited sampling of the tubes in these populations.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…15 It is important to emphasize that PAX2-null SCOUTs with normal p53 expression appear to be distributed equally in fimbrial and proximal oviductal sections, shown by Chen et al 14 and confirmed in this report. Thus, the absence of PAX2-null SCOUTs in pediatric and post-partum sterilization tubal sections is significant despite the limited sampling of the tubes in these populations.…”
Section: Discussionsupporting
confidence: 83%
“…14 However, SCOUTs were evenly distributed in the tube being no more prevalent in the fimbria than proximal segments. 14,15 From this, we concluded that SCOUTs reflected pathway disturbances that, while more prevalent in women with high-grade serous cancers, were not direct precursors to serous cancer. Nevertheless, loss of PAX2 staining was also highly prevalent in p53 signatures, secretory cell expansions with p53 mutations that are candidate precursors.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations